Pengawasan Badan Permusyawaratan Desa DalamPenggunaan Dana Desa di Desa Pretek Kecamatan Pecalungan Kabupaten Batang - deny; Syarifa Khasna (Manabia: Journal of Constitutional Law, 2022)
The Village Consultative Body, hereinafter referred to as BPD, is an institution that embodies democracy in the implementation of Village Government. The Village Consultative Body is not part of the Village Government but rather a village legislative body that works alone or independently. The Village Consultative Body is also domiciled on an equal footing and is a partner of the Village Government in organizing the Village Government. The Village Consultative Body is essentially a partner of the Village Head in carrying out the affairs of the Village Government and has an equal position in organizing government affairs, development, and community empowerment. BPD is the embodiment of democracy in the village, the democracy in question is that BPD has a strategic function in determining village policies and supervising the Village Government. These supervision efforts are intended to reduce the misappropriation of the authority of the village government in the use of village funds. This study aims to analyze the supervision of the Village Consultative Body in the use of Village Funds in Pretek Village, Pecalungan District, Batang Regency and to analyze the implications of the Supervision of the Village Consultative Body in the use of Village Funds in Pretek Village, Pecalungan District, Batang Regency for village development.